Tibial tuberosity advancement in 65 canine stifles - Hoffmann, D. E.; Miller, J. M.; Ober, C. P.; Lanz, O. I.; Martin, R. A.; Shires, P. K. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
The tibial tuberosity advancement (TTA) procedure was developed to treat dogs with cranial cruciate ligament deficient stifles. A retrospective, descriptive study was performed on 57 dogs that underwent unilateral or bilateral TTA. Medical records were reviewed and pre-, postoperative and follow-up radiographs were evaluated for patellar ligament-tibial plateau angle (α), distance of the tibial tuberosity advancement and progression of degenerative joint disease. A questionnaire was sent to all owners to obtain their assessment of the procedural outcome. Sixty-five stifles in 57 dogs received a TTA. Mean age was 5.2 ± 2.5 years while mean weight was 39.7 ± 11.9 kg. Eighteen breeds were represented with Labrador retrievers and mixed breeds predominating. The mean duration of lameness prior to surgery was 6.2 ± 6.7 months, with a median lameness score of 3/4. Fifty-nine percent of cases encountered complications, the majority of which were minor. Major post-operative complications were uncommon but consisted of implant failure, tibial crest displacement and medial meniscal tears. The mean radiographic preoperative angle α was 100°, while the postoperative was 95.5°. Mean osteoarthrosis scores were significantly different between preoperative and follow-up radiographs with 67% of cases showing radiographic progression. Seventy percent of owners responded to the survey with overall outcome considered good to excellent in 90%. Activity level was improved in 90% of responses. TTA subjectively appears to be a useful alternative in the management of cranial cruciate ligament disease. Few severe complications were encountered. Good clinical outcome and owner satisfaction was reported with the procedure in this set of cases.
Keywords: Cranial cruciate ligament; tibial tuberosity advancement; TTA; stifle